AJARAN ISLAM DALAM NASKAH SERAT SITTIN: ISLAMIC TEACHINGS IN SERAT SITTIN - Samidi Khalim (Penamas, 2014)
This article summarizes the results of philological research on the manuscript Serat Sittin. The manuscript is a collection of the Widya Budaya Museum of the Kraton Yogyakarta (code W. 306 or C. 59). Serat Sittin was written upon the initiative of Sri Sultan Hamengku Buwana V (reigned in 1823-1855) and completed on 6 July 1847. It is actually an adaptation of Sittun Mas’alah (60 religious questions), a classical Arabic work by Islamic scholar Shaikh Abu al-‘Abbās Aḥmad al-Zāhid, supplied with comments made by Aḥmad Shihabuddīn ibn Hamzah al-Ramlī. It contains various aspects of Islamic teachings, especially fiqh and tasawwuf. Serat Sittin was composed in the form of macapat (sung poetry using indigenous Javanese meters). However, in this adapted work, Islamic teachings underwent cultural pejoration, that is, the position of fiqh was considered lower than Islamic mysticism (tasawwuf). The culture of Islamic mysticism was deemed in conformity with the Javanese culture which the writer of the manuscript tended to glorify. In Serat Sittin, Islamic teachings were no longer interpreted on the basis of Islamic orthodoxy but adapted to the culture of Javanese thought. Key Words: Serat Sittin, Javanese Islam, fiqh, tasawwuf. Tulisan ini merupakan ringkasan penelitian filologis terhadap Naskah Serat Sittin. Manuskrip tersebut merupakan koleksi Museum Widyabudaya Kraton Yogyakarta dengan (kode W. 306 atau C. 59). Naskah Serat Sittin ditulis atas prakarsa Sri Sultan Hamengku Buwana V (bertahta 1823- 1855), yang selesai ditulis pada tanggal 6 Juli 1847. Naskah Serat Sittin sebenarnya merupakan saduran dari kitab kuning yang berjudul Sittun Mas’alah (60 masalah agama) karya Shaikh Abu al-‘Abbās Aḥmad al-Zāhid. Kitab tersebut kemudian diberi penjelasan oleh Aḥmad Shihabuddīn ibn Hamzah al-Ramlī. Naskah Serat Sittin berisi tentang berbagai ajaran Islam, khususnya fikih dan tasawuf. Namun ketika digubah dalam bahasa dan sastra Jawa mengalami peyorasi budaya, ilmu fikih dipandang lebih rendah daripada mistik Islam (tasawuf). Budaya tasawuf dianggap sesuai dengan budaya Jawa, sehingga tampak pengagungan terhadap budaya Jawa. Naskah Serat Sittin juga mengalami adaptasi berdasarkan kultur pemikiran Jawa, bukan atas doktrin Islam ortodoks. Kata Kunci: Serat Sittin, Islam Jawa, Fikih, Tasawuf.